Fuzzy Decision Making and Soft Computing Applications: Future Perspectives (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
This reprint explores the evolving landscape of fuzzy decision-making and soft computing techniques, offering innovative solutions for complex real-world problems. It presents future perspectives and cutting-edge applications across diverse domains, serving as a valuable resource for researchers, practitioners, and students in computational intelligence.